Pulping of Nepal Hardwoods - Guha, S. R. D.; Mathur, G. M.; Dhondiyal, S. N. (Indian Forester, 1974)
The paper contains the results of pulping of Western Nepal hardwooda, in a mixture containing 11 species by Sulphate process. The results are encouraging for making a feasibility report for a 100 tons to per day capacity paper mill in Nepal.